FILSAFAT PENDIDIKAN HUMANISTIK SEBAGAI DASAR ETIKA PENGEMBANGAN TEKNOLOGI PEMBELAJARAN DI ERA KECERDASAN BUATAN - Syahputri, Rinny; Idris, Iskandar; Ramadhan, Alfi; Yuslaili, Yuslaili (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The development of digital technology, particularly Artificial Intelligence (AI), has fundamentally transformed the landscape of education. Learning processes are no longer limited to direct interaction between teachers and students but now involve digital systems capable of personalizing materials, evaluating learning outcomes, and providing automated feedback. Although these advancements bring positive impacts in terms of efficiency and accessibility, there is growing concern that education is gradually losing its human dimension. Teachers risk being replaced by algorithms, and students may be reduced to mere data objects within machine-based learning systems. In this context, the philosophy of education plays a crucial role as the value foundation and normative direction of all educational practices. Philosophy functions not only as theoretical reflection but also as an ethical and teleological foundation that provides meaningful ultimate goals for every form of educational innovation. Among the various schools of thought, humanistic educational philosophy is the most relevant to these challenges, emphasizing the importance of freedom in learning, self-actualization, and respect for human dignity. From a humanistic perspective, education is a process of humanization the effort to nurture and develop the full potential of human beings rather than a mere transfer of knowledge. Therefore, the development of educational technology should not replace the human role but instead strengthen the essence of humanity in both learners and educators. ABSTRAKPerkembangan teknologi digital, khususnya kecerdasan buatan (Artificial Intelligence/AI), telah mengubah wajah pendidikan secara fundamental. Proses pembelajaran kini tidak lagi terbatas pada interaksi langsung antara guru dan peserta didik, tetapi melibatkan sistem digital yang mampu mempersonalisasi materi, mengevaluasi hasil belajar, bahkan memberikan umpan balik otomatis. Meskipun kemajuan ini membawa dampak positif dalam hal efisiensi dan aksesibilitas, muncul kekhawatiran bahwa pendidikan semakin kehilangan dimensi kemanusiaannya. Guru berpotensi tergantikan oleh algoritma, dan peserta didik dapat direduksi menjadi sekadar objek data dalam sistem pembelajaran berbasis mesin. Dalam konteks inilah filsafat pendidikan berperan penting sebagai dasar nilai dan arah normatif bagi seluruh praktik pendidikan. Filsafat tidak hanya berfungsi sebagai refleksi teoretis, tetapi juga sebagai landasan etis dan teleologis memberikan tujuan akhir yang bermakna bagi setiap bentuk inovasi pendidikan. Salah satu aliran filsafat yang paling relevan dengan tantangan ini adalah filsafat pendidikan humanistik menekankan pentingnya kebebasan belajar, aktualisasi diri, dan penghargaan terhadap martabat manusia. Dalam pandangan humanisme, pendidikan adalah proses memanusiakan manusia (humanisasi), bukan sekadar transfer pengetahuan. Oleh karena itu, pengembangan teknologi pembelajaran seharusnya tidak menggantikan peran manusia, melainkan memperkuat potensi kemanusiaan baik dari sisi peserta didik maupun pendidik.